2013
DOI: 10.6007/ijarems/v2-i6/442
|View full text |Cite
|
Sign up to set email alerts
|

An Investigative Study on Factors Influencing the Customer Satisfaction with E-Banking in Nigeria

Abstract: This research work intends to investigate the factors influencing the customer satisfaction with e-banking in Nigeria. The study covered twenty (20) randomly selected banks in Ibadan, Oyo state, Nigeria. A structured questionnaire was used in gathering relevant data from the bank staff and their customers respectively. 105 questionnaires were filled and returned by the respondents. The participants were drawn randomly from different departments of selected banks in Ibadan metropolis. The selection was done in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to them, dissatisfied customers can discontinue the purchase of the products, return the item and even engage in negative word-of-mouth communication. Furthermore, Alabar (2012) in Balogun et al, (2013) add that, customer satisfaction holds the potential to increase an organization's customer base, increase the use of a more volatile customer mix and increase the firm reputation. Tandoh (2020) observed that brand awareness has a significant effect on customer patronage while Yang et al, (2016) found that brand awareness can positively predict brand loyalty.…”
Section: Product Branding and Customer Patronagementioning
confidence: 99%
“…According to them, dissatisfied customers can discontinue the purchase of the products, return the item and even engage in negative word-of-mouth communication. Furthermore, Alabar (2012) in Balogun et al, (2013) add that, customer satisfaction holds the potential to increase an organization's customer base, increase the use of a more volatile customer mix and increase the firm reputation. Tandoh (2020) observed that brand awareness has a significant effect on customer patronage while Yang et al, (2016) found that brand awareness can positively predict brand loyalty.…”
Section: Product Branding and Customer Patronagementioning
confidence: 99%
“…According to Tafa (2013), e-banking has improved customer satisfaction, but the majority of the users were not actively using the services. Balogun et al (2013) carried out an investigation into the factors influencing the customer satisfaction with e-banking in Nigeria. The study found that provision of services such as simple mail service (SMS) alerts, e-mail alerts, electronic opening of account and the availability of automated teller machine (ATM) were the major factors that influence customer satisfaction.…”
Section: Customer Satisfactionmentioning
confidence: 99%